If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -6x = -61 Solving 23 + -6x = -61 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -6x = -61 + -23 Combine like terms: 23 + -23 = 0 0 + -6x = -61 + -23 -6x = -61 + -23 Combine like terms: -61 + -23 = -84 -6x = -84 Divide each side by '-6'. x = 14 Simplifying x = 14
| v(4v-24)=-6 | | -8y+5=-9y+3 | | h^2+26h-10=0 | | -6y+4=7y+5 | | 27x+13x=73 | | 3x^2-3x+5=0 | | 5p+5=7-4p | | x-2x+5=5 | | X^2+11x+13=0 | | (3x+7)(x+1)=10 | | 9-41= | | x^2-30x+125=0 | | 2x(x+8)+15=0 | | g^2-8g+11=0 | | 2x-5y=1 | | 5(x+6)=8+5x | | 3x^2+2x+8=0 | | d^2+22d+121=18 | | 8x+3y=8 | | 9x^10=4x^9+41 | | b^2-8b+17=7 | | 15x^2=3x+7 | | 4p+3=10+3p | | 4p+3=10+3 | | 7x+2y=2 | | 4x+16-18=-8x+2 | | 6.8x-1=5.8x | | 60x^2*y^4=x | | 5x+y=13 | | m^2+14=8m | | -5p^2=30p+40 | | 7(x+9)=4[x-(8-x)] |